2019
DOI: 10.29252/jafm.12.06.29757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wet Steam on Aerodynamic Performance of Low-Pressure Exhaust Passage with Last Stage Blade

Abstract: The condensation of wet steam has important effects on the behavior of the flow field. To evaluate the aerodynamic performance of exhaust passage influenced by wet steam phase change condensation, a numerical investigation was conducted. Taking a 600 MW steam turbine as an example with consideration of the wet steam from the last stage blade and the steam exhaust of the BFPT (boiler feed water pump turbine), the governing equations of wet steam two-phase flow were adopted by the Eulerian-Eulerian approach. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Then, the static pressure recovery and total pressure loss coefficients are used to characterize the performance of exhaust passage [13,14]. Lin et al [15] numerically investigated the three-dimensional flow field of exhaust hood with consideration of various inflow conditions of inlet angle, swirl strength and wetness. They found that the performance is a strong function of inflow conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the static pressure recovery and total pressure loss coefficients are used to characterize the performance of exhaust passage [13,14]. Lin et al [15] numerically investigated the three-dimensional flow field of exhaust hood with consideration of various inflow conditions of inlet angle, swirl strength and wetness. They found that the performance is a strong function of inflow conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A full-scale low-pressure (LP) cylinder of a supercritical large power steam turbine[15].98 Calculational domain of a LP exhaust passage with the addition of LSBs and extraction 100 pipelines [15]. 1.…”
mentioning
confidence: 99%
“…It compresses the incoming air through high-speed rotating blades and then enhances air pressure [1]. However, the flow loss inside the compressor is critical to the performance of aero engines under high reverse pressure gradients, especially for tip leakage flow and secondary flow [1][2][3]. Currently, the commercial codes of computational fluid dynamics are usually conducted for numerical analysis, due to the improvement of computational accuracy in the field of turbomachinery [4], flow loss [5], heat transfer [6,7], etc.…”
Section: Introductionmentioning
confidence: 99%